Haemodynamic instability in a critically ill patient with covid-19 pneumonia: searching over the chest - report of a clinical case and mini-review of the literature. Issue 2 (2020) - Conci, Simone; Ruzzenente, Andrea; Donadello, Katia; Cybulski, Adam J.; Pedrazzani, Corrado; Campagnaro, Tommaso; Schweiger, Vittorio; Dalbeni, Andrea; Mansueto, Giancarlo; Polati, Enrico; Guglielmi, Alfredo
No abstract available